Comparison of efficacy and safety of three novel hypoglycemic agents in patients with severe diabetic kidney disease: A systematic review and network meta-analysis of randomized controlled trials - Li, Yijun; Hu, Ying; Huyan, Xiaoyuan; Chen, Kang; Li, Bing; Gu, Weijun; Mu, Yiming (Frontiers in Endocrinology, 2022)
Objective: To analyze the efficacy and safety of three novel hypoglycemic agents, glucagon-like peptidyl-1 receptor agonists, dipeptidyl peptidase-4 inhibitors (DPP-4i), and sodium-glucose cotransporter two inhibitors (SGLT2i) in type 2 diabetes mellitus (T2DM) patients with severe chronic kidney disease (CKD) (defined in this study as CKD stage 3 B or above, eGFR< 45 mL/min/1.73 m²) based on important RCTs to date. Methods: We retrieved studies published before April 15, 2022, from EMBASE, PubMed/MEDLINE, Cochrane Library and included randomized controlled trials in which the participants were patients with T2DM and severe CKD. Frequentist methods were used in the network meta-analysis. Results: Nineteen studies of 17 trials involving 6,607 participants met our inclusion criteria. Compared with placebo and DPP-4i, SGLT2i demonstrated a significantly lower incidence of serious renal-related adverse events or renal death, and the odds ratios (OR) were 0.69 (0.58, 0.81) and 0.63 (0.40, 1.00), respectively. Compared with placebo, SGLT2i significantly reduced the incidence of all-cause death and severe AE; the ORs were 0.72 (0.55, 0.94) and 0.65 (0.47, 0.91), respectively. Compared with placebo, DPP-4i significantly reduced the level of HbA1c, and the difference between mean changes from baseline was -0.36 (-0.63, -0.09). Conclusions: Patients with T2DM complicated by severe CKD may benefit from SGLT2i. SGLT2i can reduce the incidence of serious renal-related AEs or renal death, as well as severe side effects, and has a positive effect on the patient's renal function and survival, even for only CKD patients can also be considered. GLP-1 RAs can be used as a supplement if blood sugar control is poor. For dialysis patients, DPP-4i can assist blood glucose control, reduce insulin dosage, and reduce the risk of hypoglycemia.